Intelligent hydrogels - Richtering, Walter (Progress in Colloid and Polymer Science,, 2013)
This volume of Progress in Colloid and Polymer Science assembles original contributions and invited reviews from the priority research program "Intelligent Hydrogels", funded by the German Science Foundation DFG since 2006, with about 25 contributing research groups. In the center of interest of this program and the present book are responsive hydrogels, i.e. hydrophilic polymer or polyelectrolyte networks that are able to respond to environmental stimuli such as changes in temperature, pH, additive concentration or electrical field. The activities focus on different aspects: on hydrogel synthesis, on the modeling and simulation of thermophysical hydrogel properties, as well as on innovative new hydrogel applications as smart materials. The present book summarizes the highlights in the results of the priority program in original contributions and invited reviews.